Interpersonal conflict and turnover intention: The mediating role of psychological well-being - Langove, N. (American Scientific Publishers, 2017)
The purpose of the study is to examine the direct effect of interpersonal conflict on turnover intention and indirect effect of psychological well-being between interpersonal conflict and turnover intention. The data was collected from IT executives working in Malaysian Software companies (n = 396). PLS-SEM technique was used to test the research model. The results of the study indicate that interpersonal conflict positively affects turnover intention while psychological well-being mediates the relationship between interpersonal conflict and turnover intention. The results revealed that the intervention of psychological well-being at workplace help to minimize the turnover intention of IT executives. Additionally, these findings might help IT practitioners to design psychological well-being policy to retain employees. This study establishes a noteworthy gap in the literature to find a mediation link of psychological well-being between interpersonal conflict and turnover intention. © 2017 American Scientific Publishers. All rights reserved.